(untitled) (Journal of Parents and Teachers, 2014)
In a changing world with great strides, vocational training is also facing major external challenges, in parallel to a rapid internal transformation process: the implementation of basic vocational training LOMCE, the implementation of the dual training, the rapid increase in demand, the increasing age of the students ... the question arises whether challenges and changes going in the same direction?